Contribution of Researchers of the Institute of Geography of the NAS of Ukraine in the Field of Nature Management and Sustainable Development - Lisovskyi, S. A.; Rudenko, L. H.; Maruniak, Eu. O.; Gukalova, I. V. (Ukrainian Geographical Journal, 2024)
The purpose of the article is to provide a comprehensive analysis of the research results of the Institute of Geography of NASU on the problems of environmental management and sustainable development, as well as to identify the priority and most relevant areas for further development in this area. The paper considers research carried out in the Institute’s departments since its foundation, focusing on the development of a significant number of methodologies and their application. A chronological analysis of the Institute of Geography’s developments in environmental management and sustainable development has been conducted. Their interconnection and priority of the areas on which the developments were focused in accordance with the needs to respond to the challenges and most pressing risks in different years, taking into account the impact of internal and external factors, have been highlighted. The novelty of the work is determined by the analysis of the developments of the Institute of Geography on the study of the consequences of Russian aggression for the population, economy, and nature of Ukraine and its regions, the possibilities of overcoming them to ensure the country’s further progress based on sustainable (balanced) development. It is emphasized that the results of the Institute’s research on the issues of rational nature management and sustainable development have been widely used in the work of the central executive authorities of Ukraine, ministries in particular the Ministry of Community Development, Territories and Infrastructure of Ukraine, the Ministry of Environmental Protection and Natural Resources of Ukraine, other ministries and agencies, regional state administrations, etc. The analysis of the Institute’s research on improving the methodology of landscape planning and strategic environmental assessment indicates the pioneering nature of this research in Ukraine. The novelty of the work is also determined by the analysis of developments in the study of the consequences of Russian aggression for Ukraine’s population, economy, and nature, as well as the possibilities for overcoming them to ensure the country’s further progress based on sustainable (balanced) development.